Mentoring Through Education Diplomacy - Georgianna Duarte Dr. (Academic Chairpersons Conference Proceedings, 2018)
The presenters and participants will explore the conceptual framework of education diplomacy as a model for mentoring faculty in areas of inquiry, negotiation, humor, and mediation.
Keywords: Education Diplomacy; Global Cultural Competency; departmental culture